Efficient recruitment with effective job advertisement: an exploratory literature review and research agenda. Issue 2 (22nd March 2021) - Mahjoub, Ali; Kruyen, Peter Mathieu
Abstract : Purpose: This article presents an exploratory, narrative review on job ads research. It aims to explore the key features of job ads that have been investigated in previous researches; the way these features have been investigated; and to draw important lessons that those studies teach us about the impact of job ad features on the target population. Design/methodology/approach: In this study, the scoping-review procedure is applied. Its systematic procedure enables scholars to provide a broad overview of a topic, map the key concepts underpinning a research area, clarify the conceptual boundaries of a topic, and also to incorporate a numerical summary and qualitative thematic analysis. The review was conducted based on a systematic study of 243 peer-reviewed articles and publications in the grey literature. Findings: The findings show that seven job ad features seem to have important impacts on (potential) applicants, which we illustrate as a know-how framework. Eight main theories are used, and a wide array of research methods are applied. However, the study concludes that after more than four decades of research, there is still a limited understanding about the concrete effects of job ad features. Originality/value: This paper synthesizes the existing knowledge, answers three exploratory questions regarding job ad features and draws theoretical and practical lessons from previous studies. In the interest of conducting future studies and providing a research agenda, a typology of theoretical perspectives for the study of job ads is also presented. The article also presents lessons for practitioners by providing a know-how framework on the usage of job ads.